Inhibiting autophagy targets human leukemic stem cells and hypoxic AML blasts by disrupting mitochondrial homeostasis - Dykstra, Kaitlyn M. (Blood Adv, 2021)
Leukemia stem cells (LSCs) and therapy-resistant acute myeloid leukemia (AML) blasts contribute to the reinitiation of leukemia after remission, necessitating therapeutic interventions that target these populations. Autophagy is a prosurvival process that allows for cells to adapt to a variety of stressors. Blocking autophagy pharmacologically by using mechanistically distinct inhibitors induced apoptosis and prevented colony formation in primary human AML cells. The most effective inhibitor, bafilomycin A1 (Baf A1), also prevented the in vivo maintenance of AML LSCs in NSG mice. To understand why Baf A1 exerted the most dramatic effects on LSC survival, we evaluated mitochondrial function. Baf A1 reduced mitochondrial respiration and stabilized PTEN-induced kinase-1 (PINK-1), which initiates autophagy of mitochondria (mitophagy). Interestingly, with the autophagy inhibitor chloroquine, levels of enhanced cell death and reduced mitochondrial respiration phenocopied the effects of Baf A1 only when cultured in hypoxic conditions that mimic the marrow microenvironment (1% O(2)). This indicates that increased efficacy of autophagy inhibitors in inducing AML cell death can be achieved by concurrently inducing mitochondrial damage and mitophagy (pharmacologically or by hypoxic induction) and blocking mitochondrial degradation. In addition, prolonged exposure of AML cells to hypoxia induced autophagic flux and reduced chemosensitivity to cytarabine (Ara-C), which was reversed by autophagy inhibition. The combination of Ara-C with Baf A1 also decreased tumor burden in vivo. These findings demonstrate that autophagy is critical for mitochondrial homeostasis and survival of AML cells in hypoxia and support the development of autophagy inhibitors as novel therapeutic agents for AML.